1999
DOI: 10.1038/sj.onc.1203006
|View full text |Cite
|
Sign up to set email alerts
|

17q21-q25 aberrations in breast cancer: combined allelotyping and CGH analysis reveals 5 regions of allelic imbalance among which two correspond to DNA amplification

Abstract: Chromosome 17q is frequently rearranged in breast cancer. Allelotyping studies have proposed the existence of at least four regions of allelic imbalance (AI). Here we present a study combining allelotyping using 19 CA repeat markers mapping in the 17q21 ± 25 region and molecular cytogenetics (CGH and FISH). Allelotyping was undertaken on 178 pairs of cognate tumor and normal DNA in order to determine the number of regions of AI and de®ne the shortest overlaps. AI ranged from 34 ± 54% of the informative cases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 22 publications
2
35
0
Order By: Relevance
“…The NHERF gene is mapped at 17q25, a region that undergoes frequent allelic loss in breast and ovarian cancer (Radford et al, 1995;Kalikin et al, 1996Kalikin et al, , 1997Plummer et al, 1997;Orsetti et al, 1999;Harkes et al, 2003). LOH involving this locus was determined with three highly polymorphic markers (D17S785, D17S801, and D17S1351) that neighbored the NHERF gene.…”
Section: Mutational Analyses Of Nherf Genementioning
confidence: 99%
“…The NHERF gene is mapped at 17q25, a region that undergoes frequent allelic loss in breast and ovarian cancer (Radford et al, 1995;Kalikin et al, 1996Kalikin et al, , 1997Plummer et al, 1997;Orsetti et al, 1999;Harkes et al, 2003). LOH involving this locus was determined with three highly polymorphic markers (D17S785, D17S801, and D17S1351) that neighbored the NHERF gene.…”
Section: Mutational Analyses Of Nherf Genementioning
confidence: 99%
“…In sporadic forms of breast cancer, a number of ampli®ed or deleted chromosome regions have been identi®ed using techniques, which test for allelic imbalance (Bieche et al, 1999;Bonsing et al, 2000;Orsetti et al, 1999;Osborne and Hamshere, 2000;Rodriguez et al, 2000;Sta et al, 2000). In high-grade breast cancer, chromosome regions that are ampli®ed leading to protein overexpression, often include genes coding ErbB2, c-Myc and Cyclin D1 (Brison, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of the CNVs for such genes is a starting point for investigations into the role of gene amplification in the colorectal carcinogenic process. Although a number of studies showed that the chromosome 17q21 region encompassing HER-2 was amplified in breast cancer samples (14)(15)(16)(17), the correlation between CNVs and HER-2 overexpression in CRC has yet to be elucidated. In this study, 134 CRC (adenocarcinomas) samples were collected for CNV analysis of HER-2.…”
Section: Discussionmentioning
confidence: 99%
“…The role of copy-number variations (CNVs) in various types of cancer has become a hot spot over the past few years (12,13). Studies using SNP arrays and aCGH have suggested that DNA amplification at chromosome position 17q21, the chromosomal locus of HER-2, is common in breast cancers (14)(15)(16)(17). However, the correlation between CNVs and HER-2 overexpression in CRC has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%